A systematic review of counselling lesbian, gay, bisexual and transsexual (LGBT) individuals - Wong, Wing Hoe; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2017)
A systematic review of the literature in the area of counselling lesbian, gay, bisexual, and transsexual (LGBT) individuals was carried out with searches in five databases using a single standardized search engine. The review was conducted to understand aspects pertinent to the counselling services provided to the LGBT community as a category of multicultural diversity. The aspects this systematic review researched into are as follows: (1) Insights of the LGBT community, (2) Issues and challenges faced by LGBT individuals, and (3) Effective counselling interventions for LGBT individuals. Results from the literature review indicate that there are four peculiar domains revolving the counselling practice of LGBT individuals: psychological, social, economic, and physical. These domains are interrelated in determining the total wellbeing of an LGBT individual. Therefore, counsellors’ recognition and understanding on these domains in terms of multicultural diversity is imperative in the effort of providing effective counselling services to the LGBT community.